Da Dominikanerordenen kom til Danmark: Om kilderne til den dominikanske klosterstiftelse i Lund 1222 - Jakobsen, Johnny Grandjean Gøgsig (Kirkehistoriske Samlinger, 2022)
I 2022 er det 800 år siden, at det første dominikanerkloster blev oprettet i Danmark, hvilket fandt sted i ærkebispestaden Lund. Det samme kan man i realiteten sige for hele Norden, for ganske vist havde ordenen forsøgt at etablere et hus i Sverige to år forinden, men det blev opgivet igen efter få år. Om det nu også virkelig var i 1222, at det første blivende dominikanerkloster blev oprettet, har dog været diskuteret, og også årene 1221 og 1223 har været foreslået. Årsagen til usikkerheden er, at hovedkilden til begivenheden nok oplister en række årstal, men ikke fuldstændig eksplicit for lige præcis klosterstiftelsen, hvor kildeteksten faktisk synes at modsige sig selv. Kilden, der er en krønike skrevet af Dominikanerordenen selv, rummer flere andre problemer og bør som alle andre historiske kilder indtages med et kildekritisk gran salt, men dens oplysninger om ordenens tidligste ankomst til Norden understøttes faktisk af flere andre uafhængige kilder. Denne lille ‘jubilæumsartikel’ vil søge at redegøre for Dominikanerordenens ankomst til Norden og for de tilgængelige kilder dertil. Summary The first Dominican friary in medieval Denmark was founded in 1222. It was also the first lasting friary of the Dominican Order to be established in its Scandinavian province of Dacia. Essentially, this is the core historical facts to be gained from reading this article. The aim of the article is, however, to go a little beyond the mere events of this monastic foundation, which now happens to celebrate its 800th anniversary, by adding a thorough presentation and even discussion of the sources to it. For a monastic institution in medieval Scandinavia, the history of the foundation of the Dominican friary in Lund is unusually well-documented. Not only do we have an almost contemporary chronicle written by friars of the order itself to provide us with a broad set of details on how the convent came about to be established. Several of the facts claimed by the chronicle are even collaborated by a variety of independent extant sources. Still, as is often is with medieval studies, an abundance of sources does not necessarily make it easier for present-day historians to figure out what actually happened, since medieval documents have a curious tendency of somewhat contradicting each other and even themselves. That is certainly the case with the history of the Dominican convent foundation in Lund, for which even the stated year of the event, 1222, is up for debate. The present article lists all available sources to what can be said about the foundation and the first three friars involved with it, as well as some of the various twists and angles that later historians have exposed these sources to in a common goal of getting closer to ‘the historical truth’.